Estudo piloto sobre diâmetro do canal lombar e distância percorrida em pacientes com estenose espinhal lombar: um modelo de predição multivariado - Singh, Gurjant; Chahal, Aksh; Singh, Manjeet (Revista Pesquisa em Fisioterapia, 2022)
INTRODUCTION: Neurogenic claudication (NC) is the classic clinical presentation of patients with Lumbar Spinal Stenosis (LSS). These patients may or may not present with symptoms of leg pain and difficulty walking. These symptoms are exacerbated while walking and standing and are eased by sitting or bending forward. METHOD: Patients with LSS, having a lumbar canal diameter of less than or equal to 12mm, were recruited from a recognized Tertiary care hospital. Each subject’s demographic characteristics and anthropometrics were noted, and the testing procedure was explained. The canal diameter was documented with the help of an MRI report. A self-paced walking test was used to assess the walking distance. STATISTICAL ANALYSIS: Depending on the normality of the data, the Pearson correlation coefficient (r) was used to find the correlation between canal diameter at different lumbar levels and walking distance in patients with LSS. RESULT: Pearson correlation coefficient (r) determined a fair positive correlation (r = 0.29) between lumbar canal diameter and walking distance. Stepwise multiple regression analysis was done, and a prediction equation was found for different levels of canal stenosis. CONCLUSION: Findings of our present study suggest a fair positive correlation between walking distance and canal diameter at L5-S1. This study may also be useful in predicting the approximate canal diameter by estimating the walking distance of the patient with symptoms of LSS and vice-versa.